Tragedy, ritual and money in ancient Greece : selected essays - Seaford, Richard; Bostock, Robert (Cambridge : Cambridge University Press, 2018)
Richard Seaford is one of the most original and provocative classicists of his age. This volume brings together a wide range of papers written with a single focus. Several are pioneering explorations of the tragic evocation and representation of rites of passage: mystic initiation, the wedding, and death ritual. Two papers focus on the shaping power of mystic initiation in two famous passages in the New Testament. The other key factor in the historical context of tragedy is the recent monetisation of Athens. One paper explores the presence of money in Greek tragedy, another the shaping influence of money on Wagner's Ring and on his Aeschylean model. Other papers reveal the influence of ritual and money on representations of the inner self, and on Greek and Indian philosophy. A final piece finds in Greek tragedy horror at the destructive unlimitedness of money that is still central to our postmodern world.
Title from publisher's bibliographic system (viewed on 16 Nov 2018).
Keywords: Greek literature -- History and criticism; Greek drama (Tragedy) -- History and criticism; Rites and ceremonies in literature; Money in literature; Economics and literature -- Greece